Differences in prevalence of overweight and stunting in 11-year olds across Europe: The Pro Children Study. - Yngve, Agneta (2008)
Objectives: To assess country differences in prevalence of overweight, obesity, underweight and stunting in the Pro Children Survey. Methods: A cross-sectional study conducted in a random sample of schools in nine European countries in 2003. The subjects were 8317 11-year-old children from Austria, Belgium, Denmark, Iceland, The Netherlands, Norway, Portugal, Spain and Sweden. Parents reported height and weight of the children, and BMI values were analysed using the US Centers of Disease Control and Prevention and the International Obesity Task Force reference populations. Continuous variables were compared with one-way analysis of variance (ANOVA) with Games-Howell post hoc tests. Categorical variables were analysed using chi-square tests. Results: The prevalence of overweight + obesity varied between the countries from 8.6% to 30.6% and 5.9% to 26.5%, respectively, depending on the reference population, with the lowest prevalence in Dutch girls, the highest in Portuguese boys. Obesity prevalence varied from 1.1% (Dutch and Danish girls) to 10.7% (Portuguese boys) and from 0.3% (Dutch girls) to 6.2% (Portuguese boys), respectively. Portugal and Spain had the highest prevalence of overweight and obesity for both genders. The ranking of the countries according to overweight and obesity prevalence was roughly the same, independent of reference population. The prevalence of underweight varied from 2.3% (Swedish boys) to 12.3% (Belgian boys), using the American reference population. The proportion of stunted children was highest in Portugal, Spain and Belgium. Conclusions: The highest levels of overweight, obesity and stunting in the pro children material are found in Portugal and Spain. Keywords: childhood, Europe, growth, short stature